Insiders versus outsiders interest group politics in multilevel Europe - Dür, Andreas 1976-; Mateo González, Gemma (Oxford University Press, 2016)
What explains differences in the lobbying behaviour of interest groups? And what consequences do these differences have for the access that interest groups can gain to decision-makers and the influence that they can exert on policy outcomes? Building on an unprecedented amount of empirical evidence on lobbying in Europe, this book puts forward a distinction between lobbying insiders and lobbying outsiders. Lobbying insiders, most prominently business interests, try to establish direct contacts with decision-makers, enjoy good access to executive institutions, and manage to shape policy outcomes when mobilizing the public on an issue is difficult. Lobbying outsiders, in particular citizen groups such as consumer, environmental or health non-governmental organizations, put greater emphasis on mobilizing the public or changing public attitudes, find it easier to gain access to legislative decision-makers, and have the greatest impact on outcomes on issues that are amenable to an outside lobbying campaign. The book shows that a single argument, building on group types as the main variable, can explain variation across interest groups in their choice of strategy, their access to decision-makers, and the conditions under which they can exert influence